Physical fitness and hematological changes during acclimatization to moderate altitude: A retrospective study - Brothers, M. D.; Wilber, R. L.; Byrnes, W. C. (High Altitude Medicine & Biology, 2007)
While high altitude adaptations have been studied extensively, limited research has examined moderate altitude (MA: 1500 to 3000 m) adaptations and their time course, despite the fact that millions of people sojourn to or reside at MA. We retrospectively examined long-term MA acclimatization by analyzing recurring physical fitness test results and hematological data among 2147 college-age male cadets previously residing at either sea level (SL) or MA and currently attending the U.S. Air Force Academy (USAFA), a unique, regimented, and well-controlled military university located at 2210 m. Significant (p < 0.01) differences were found in aerobic and anaerobic fitness test scores between former SL and MA subjects, with MA subjects scoring 27 points (8%) higher during a 1.5-mile aerobic fitness run and 18 points (6%) higher than SL subjects in the anaerobic fitness test for 2 yr. These differences may be partly explained by the hematological differences observed. Hemoglobin concentration ([Hb]) was significantly (p < 0.001) higher (6.3%; 1 g/dL) in MA subjects prior to arrival at USAFA and acutely, but the difference between altitude conditions was gone at the next retrospective blood draw (+17 months). After 2.5 yr at USAFA, former SL residents had significantly (p < 0.001) higher [Hb] by +10%, or 1.5 g/dL versus prearrival values. This study suggests that significant hematological acclimatization occurs with MA exposure and requires greater than 7 months to reach stability. The altitude-induced erythropoiesis may explain in part the improvements in aerobic performance, but altitude-related anaerobic differences still remain after hematological acclimatization.